Theodicy and spirituality in the fourth gospel a Girardian perspective - London, Daniel DeForest (Lexington Books/Fortress Academic, 2020)
"This book argues that the Fourth Gospel offers a potentially transformative response to the question of suffering and the human compulsion to blame. By engaging with the symbols of light, vision, and the Good Shepherd, readers can experience a theodical spirituality that transforms resentment and rage through divine forgiveness"--
Originally published as Where lambs may wade and wolves can swim (PhD--Graduate Theological Union, 2016)
Keywords: Girard, René -- 1923-2015; Bibel -- Johannesevangelium; Theodizee; Spiritualität; Bible / John / Criticism, interpretation, etc; Suffering / Religious aspects / Christianity; Blame / Religious aspects / Christianity; Mimesis in the Bible; Spiritual life / Christianity; Girard, René / 1923-2015; Bible / John; Criticism, interpretation, etc